Analysis of Performance Comparison between K-Nearest Neighbor (KNN) Method and Naïve Bayes Method in Reward for Honda Motorcycle Salesman Tour - Fawaz, Muhammad Ayyasi; Khairul , Khairul; Siahaan , Andysah Putera Utama (Sinkron : jurnal dan penelitian teknik informatika, 2024)
Honda Indako Trading Coy Krakatau is a company in the automotive and spare parts industry. As the main dealer of Honda motorcycles and spare parts for North Sumatra and Aceh, the company faces challenges in boosting sales and maintaining employee loyalty. To address this, the company offers a reward salesman tour for employees who meet certain criteria. However, the current evaluation system is too simple and does not fully capture the quality of employees, especially their product knowledge and involvement in company campaigns. This study aims to solve these issues using data mining techniques, specifically the Naïve Bayes and K-Nearest Neighbors (KNN) methods. These methods were chosen for their accuracy and simplicity. The K-Nearest Neighbor method (K=11) showed an accuracy of 94.04%, a precision of 83.78%, and a recall of 96.87%, while the Naïve Bayes method showed an accuracy of 81.81%, a precision of 72.00%, and a recall of 81.25%.